Ecotourism Policy Supported By Environmental Planning Procedure - An Environmental Planning Experience. Case Of Identification Of Igneada As An Eco-Town - Çevik, Gülay; Gökdemir, M.; Eren, Z. O.; Korkmaz, Z.; TÖRE, EVRİM ÖZKAN (Scibulcom Ltd, Po Box 249, 1113 Sofia, Bulgaria, 2012)
Tourism demand is mainly generated by environmental assets, natural beauties, and cultural heritage. To perpetuate the tourism demand these assets, potentials must be preserved for forthcoming generations. This vicious cycle leads us to the importance of use and preservation balance approach and the issue of sustainability and corporate social responsibility which are crucial to sustainable tourism. In this frame, Igneada, located on the skirts of the Istiranca mountains and on the Black Sea coast, has great potantials. In this study, the existing socio-economical conditions of local people and the potentials of Igneada for ecotourism are examined and the alternative ecotourism activities and ecotourism products using the local potentials for Igneada (and the nearby villages) are given. The case of Igneada is examined regarding the 1/25 000-scaled Environmental Plan decisions of the city of Kirklareli as a considerable step in legalisation towards its identification as an eco-town.
Keywords: Sustainable Tourism; Eco-Town; Igneada; Environmental Plan; Alternative Eco-Tourism Activities; Sürdürülebilir Turizm; Eko-Kent; İğneada; Çevre Planı; Alternatif Eko-Turizm Faaliyetleri